فجوة الحبوب وإستراتيجية الأمن الغذائي في العراق للمدة (2000-2013) (المجلة العراقية للعلوم الاقتصادية, 2018)
The nutrition gap of strategic crops is one of the main indicators that reflect the extent of which the local production of such crops meet the local consumption demands. In addition, it exposes the failure of the agricultural policies adopted by the government, as well as it reveals the risks of reliance on importing strategic crops from world markets, the consequent political and economic dependency, and the country's loss of hard currency that should have been spent in the process of development. The importance of this aspect has increased since such products, in addition of being food, have turned into political goods. As regards the gap estimations, the future forecasting of the nutrition gap of strategic crops, it is one of the necessary procedures due to its essential value of guiding the state while setting up policies that intend to solve the food problem in the future. This can be done through adopting agricultural and economic policies that guarantee solving the problems that block the way to developing and improving the production of those strategic crops.